CN102296174 (2011)
The invention provides an energy-saving combined ore dressing process for high-oxidation and high-bonding oxygen and sulfur mixed copper ore. The process comprises the steps of raw ore treatment, preparation of leaching solution, stirring and leaching, dynamic soaking selection, solid-liquid separation and washing and filtration of leached residue. The ore is crushed till the granularity is less than 10 millimeters, and the crushed ore with granularity of less than 3 millimeters is screened; sulfuric acid solution, the PH of which is less than 8, is used as the leaching solution; the raw ore is dynamically and continuously soaked for less than 24 hours, and the leachate is directly guided to an extraction process after PH value neutralization and micro pipe filtration; and the leached residue is separated by using a belt filter, and the filtered residue is treated in a flotation process to extract copper sulfide ore. According to the combined efficient washing and filtering process, dynamic soaking is adopted, the leachate is subjected to micro pipe filtration (the leachate with solid concentration of less than or equal to 3 percent in liquid can be filtered, and the solid content of the filtered liquid can be less than 50ppm), and the leached residue is separated by using the belt filter, so that the ore can meet the process requirement without fine crushing. By the process, the metal recovery rate of the high-bonding oxidized copper ore reaches over 80 percent, continuous production is realized, and energy consumption and production cost are comprehensively reduced.